Study on Micro-structure, Hardness and Optimization of Wear Characteristics of Al6061/TiB2/CeO2 Hotrolled MMCs using Taguchi Method (Fracture and Structural Integrity, 2023)
Aluminium composites are extensively used in several industrial applications. The production of Metal Matrix Composite (MMCs) with varying wt. % of reinforcement/s leads to enhancement of wear and mechanical behavior. In the present work, the varying wt. % of TiB2 and constant wt. % of CeO2 particulates were reinforced in Al6061 alloy to manufacture hybrid Al MMCs by Vortex (Stircasting) technique. Developed hybrid MMCs were hotrolled at 515°C of temperature. Hardness of hybrid MMCs was evaluated by using hardness test rig (Vickers). Result revealed that the hardness strength of developed hybrid MMCs increased with increase of the reinforcement content. The rate of wear of developed hybrid MMCs was evaluated by using Pin on Disc wear test. Test trials were conducted according to Taguchi technique. L27 array was implemented for evaluation of data. Effect of varying factors on the rate of wear and COF was analyzed by applying ANOVA (Analysis of Variance) method. ANOVA outcomes showed that the reinforcement content had a more significant impact on wear behavior and COF of the MMCs. Finally, L27 array outcomes were verified through confirmation experiments. A wear fractography outcome shows the internal fractured structure of a wear specimen which was studied using a SEM.
Keywords: Al6061; TiB2-CeO2; Stir casting; Hot rolling; Hardness; Wear behavior; Taguchi technique; Fracture behavior